2019
DOI: 10.1038/s41467-019-09399-0
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of redox mediators in lithium-oxygen batteries by singlet oxygen

Abstract: Non-aqueous lithium-oxygen batteries cycle by forming lithium peroxide during discharge and oxidizing it during recharge. The significant problem of oxidizing the solid insulating lithium peroxide can greatly be facilitated by incorporating redox mediators that shuttle electron-holes between the porous substrate and lithium peroxide. Redox mediator stability is thus key for energy efficiency, reversibility, and cycle life. However, the gradual deactivation of redox mediators during repeated cycling has not con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 62 publications
0
89
0
Order By: Relevance
“…However, fluorescence quenching of DMA has not always been unambiguously observed during oxygen reduction in aprotic solvents containing lithium, although the detection of the endoperoxide at high DMA concentrations revealed the formation of 1 O 2 during Li‐O 2 cell discharge . Deactivation of redox mediators in lithium‐oxygen batteries by singlet oxygen has also been recently reported . Freiberg et al.…”
Section: Figurementioning
confidence: 99%
“…However, fluorescence quenching of DMA has not always been unambiguously observed during oxygen reduction in aprotic solvents containing lithium, although the detection of the endoperoxide at high DMA concentrations revealed the formation of 1 O 2 during Li‐O 2 cell discharge . Deactivation of redox mediators in lithium‐oxygen batteries by singlet oxygen has also been recently reported . Freiberg et al.…”
Section: Figurementioning
confidence: 99%
“…[134,135] What's more, the majority of RMs suffers from severe decomposition toward singlet oxygen. [35,136] Therefore, to improve the efficiency of RM and battery stability, the exploration of RM immune from side reactions should be emphasized first. RM shuttling effect need to be avoided as well, using appropriate separation such as ceramic solid electrolyte, [135] metal-organic framework (MOF) separator, [137] and Al 2 O 3 /PVDF-HFP composite protective layer.…”
Section: Redox Mediatormentioning
confidence: 99%
“…Reproduced with permission. [35] Copyright 2019, Springer Nature. (Figure 9f,g), suggesting predominant cause for RM deactivation to be 1 O 2 .…”
Section: Singlet Oxygen: the Real Culprit For Parasitic Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been recently demonstrated that the evolution of singlet oxygen during operation of Li-O 2 cell also leads to the degradations of cell components, reactive oxygen radical species remain one of the main causes of parasitic reactions, prohibiting the use of conventional electrolytes and air electrodes. [32][33][34][35][36] A breakthrough in the suppression of these side reactions is thus imperative to achieve stable operation of Li-O 2 batteries.…”
mentioning
confidence: 99%